Acute appendicitis and ulcerative colitis: a population-based sibling comparison study - Scott Montgomery; Ayako Hiyoshi; Miguel Garcia-Argibay (BMJ Open Gastroenterology)
Objective To assess the inverse relationship between acute appendicitis and ulcerative colitis (UC) using a sibling comparison design to adjust for unmeasured familial genetic and environmental factors.Design The cohort comprised 3.1 million individuals resident in Sweden between 1984 and 2018 with the linkage of several Swedish national registers. Fitting Cox hazards models, we calculated the risk for developing UC in individuals with and without acute appendicitis by the age 20 years adjusting for several potential confounding factors. Further, we performed sibling-stratified analyses to adjust for shared unmeasured familial confounding factors.Results During 57.7 million person-years of follow-up, 20 848/3 125 232 developed UC among those without appendicitis (3.63 (3.59–3.68) per 10 000 person-years), whereas only 59/35 848 people developed UC among those with appendicitis before age 20 years (1.66 (1.28–2.14) per 10 000 person-years). We found a decreased risk for developing UC in those with acute appendicitis by the age 20 years compared with individuals who did not have appendicitis by this age (HR=0.37 (95% CI 0.29 to 0.48)). When adjusting for shared familial confounders, we observed only a slight attenuation in this association (HR=0.46 (95% CI 0.32 to 0.66)).Conclusion Individuals who had acute appendicitis by late adolescence showed a decreased risk for developing UC compared with those who did not. Genetic and shared familial environmental factors seem to potentially play only a small role in this relationship. Our results suggest an independent association of acute appendicitis, or its underlying causes, with UC risk.